Acceptance and Nutritional Value of Cookies Substituted with Tuna Fish Meal Madidihang (Thunnus Albacares) - ., Fatmawati; ., Kartini; Aisa, Siti (KnE Life Sciences, 2019)
The present research aimed to investigate the acceptance and nutritional value of cookies substituted with tuna fish meal madidihang (thunnus albacares). This was a pre-experiment. Data were collected in the form of primary data, namely the acceptance of cookies using organoleptic assessment including the acceptability of color, taste, aroma, and texture. The nutritional value of cookies is carried out in the nutrition laboratory. The data were analysed by Kruskal Wallis’ tests. The research result indicates that the nutritional value of thunnus albacares bone meal per 100 grams carries a calcium content of 19.28%, cabbage is 14.06%, fat 6.52%, protein 23.41%, water 4.49%, and ash 51.52%. There is no difference in the acceptability of color, aroma, and taste of cookies substituted with thunnus albacares at concentrations of 10%, 15%, and 20%. There is a difference in the acceptability of the texture of cookies substituted with Midnight tuna (thunnus albacares) at concentrations of 10%, 15%, and 20% (p = 0.023). The preferred texture acceptability is at a concentration of 15%.